Analisis Perbandingan Kinerja UMKM Berdasarkan Kepemilikan Informasi Keuangan di Kabupaten Mimika - Melfi Okviani Mananta; Ignasius Narew (STIE Jambatan Bulan, 2023)
This study aims to find out: Knowing what factors influence the use of financial information and comparing the performance of MSMEs based on ownership of financial information. The population in this study is MSME actors who use financial reports and MSMEs who do not use financial statements, the sample taken amounted to 100 businesses. Instrument trials are carried out using analysis techniques, t difference test two independent samples and factor analysis. The results showed that from the testing of factor analysis, there are 3 factors that affect the use of accounting information including business scale, usefulness, and knowledge. Furthermore, there are 4 factors that affect MSMEs that do not compile financial statements including habits, business scale, knowledge and usefulness. From the financial performance comparison test, there is a comparison of financial performance between MSMEs that use financial information and MSMEs that do not use financial information